2011
DOI: 10.2516/ogst/2010031
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Role of Reaction Modeling in Multi-phase CFD-based Simulations of Chemical Looping Combustion

Abstract: Résumé -Impact du modèle de réaction sur les simulations CFD de la combustion en boucle chimique -La combustion en boucle chimique (Chemical Looping Combustion) est une technologie de combustion efficace permettant le captage in situ du CO 2 pour des charges gazeuses ou solides. Dans l'optique du développement et de l'extrapolation du procédé, la CFD est un outil de simulation à fort potentiel qui s'appuie notamment sur des modèles cinétiques pour décrire les réactions gaz-solide. Ces modèles décrivant les réa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Similar simulations were conducted by Jung and Gamwo [20] for the reaction between NiO and methane, Wang et al [21] for the reaction between NiO and methane, and Wang et al [22] for the reduction reaction between CuO/Al 2 O 3 oxygen carrier and coal gas containing CO, H 2 , H 2 O and CO 2 . Kruggel-Emden et al [23] investigated the validity of the heterogeneous reaction kinetics models by conducting a CFD simulation in the FR; the results revealed that the empirical polynomial based models proposed by Kruggel-Emden et al [24] provide an accurate representation to the reaction rate.…”
Section: Introductionmentioning
confidence: 98%
“…Similar simulations were conducted by Jung and Gamwo [20] for the reaction between NiO and methane, Wang et al [21] for the reaction between NiO and methane, and Wang et al [22] for the reduction reaction between CuO/Al 2 O 3 oxygen carrier and coal gas containing CO, H 2 , H 2 O and CO 2 . Kruggel-Emden et al [23] investigated the validity of the heterogeneous reaction kinetics models by conducting a CFD simulation in the FR; the results revealed that the empirical polynomial based models proposed by Kruggel-Emden et al [24] provide an accurate representation to the reaction rate.…”
Section: Introductionmentioning
confidence: 98%
“…Nam et al [41] performed a CFD simulation to predict the effects of different jet/grid air ratio and pressure conditions on the hydrodynamics characteristics of a pilot-scale pressurized fluidized bed gasifier. By far, the simulation studies with CFD method on CLC mainly focus on the gas-fueled CLC [42][43][44][45][46][47][48][49][50][51][52] and fluid dynamics in CLC systems [53][54][55][56], and only a few of them have probed into the field of solid-fuel CLC. Mahalatkar et al [57] pioneered the prediction of solid-fuel CLC performance in the fuel reactor using a two-dimensional model.…”
Section: Of 17mentioning
confidence: 99%
“…Moreover low fuel gas conversions were predicted due to the bubbles formed and the reacting gas bypassing the solid inside the bubbling bed. Kruggel-Emden et al [9], Mahalatkar et al [10] also conducted studies of the reactive performance of the CLC system. The simulation studies mentioned above were limited to the fuel reactor only, but a few authors have also carried out the full loop simulation of the CLC process.…”
Section: Introductionmentioning
confidence: 99%